Microeconomic Simulator of Firm Behavior under Monopolistic Competition - ANGELOV, Aleks; VASILEV, Aleksandar (Journal of Research in Educational Sciences; Vol 8 No 10 (2017): Volume VIII, Issue 10, 2017, 2018)
Computer simulators are proving to be indispensable education tools as they enable their users to readily apply theoretical knowledge and to automatically receive immediate feedback, which is invaluable both to learners and to their instructors. Yet at present, there is virtually no publically available software for teaching economics to people who are new to this discipline. The Microeconomic Simulator of Firm Behavior under Monopolistic Competition is an interdisciplinary project which tries to fill this niche by providing an interactive means of strengthening and assessing a person’s grasp of fundamental economic concepts. It simulates the dynamic conditions of real-world markets that exhibit characteristics both of monopoly and of perfect competition, and demonstrates how choices made by a company’s executives affect its profitability. This is done in an intuitive manner through a user-friendly web application, which can be accessed from any device with an HTML5-compliant browser. The application is based on a proprietary algorithm which transforms the abstract economic model of monopolistic competition into a series of easy-to-follow steps and supplies diagrams and pop-ups, which help users comprehend the consequences of their actions. The parameters of the model are fully customizable so that different economic environments can be explored. After the end of a simulation, users are presented with a summary of their performance, which they can use to measure their progress over time, or to see how they rank among their peers.